2016
DOI: 10.1371/journal.pone.0149783
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inflammation by IL-17A and IL-17F Modulates Non-Alcoholic Fatty Liver Disease Pathogenesis

Abstract: Non-alcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease worldwide. While it is well-accepted that inflammation is central to NAFLD pathogenesis, the immune pathway(s) orchestrating disease progression are poorly defined. Notably, IL-17RA signaling, via IL-17A, plays an important role in obesity-driven NAFLD pathogenesis. However, the role of the IL-17F, another IL-17RA ligand, in NAFLD pathogenesis has not been examined. Further, the cell types expressing IL-17RA and producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 46 publications
3
98
0
1
Order By: Relevance
“…RNA was extracted from lysed tissue samples, and cDNA was transcribed according to previously described protocol [23], [24]. qPCR analysis was then completed utilizing a Light Cycler 480 II (Roche), Sybr Green I Master mix (Roche) and the following primers pairs: Abca1 For GCTGCAGGAATCCAGAGAAT Rev CATGCACAAGGTCCTGAGAA; Mmp2 For GATGGCATTCCAGGAGTCTG Rev CCAGCAAGTAGATGCTGCCT; Rag1 For CTGAAGCTCAGGGTAGACGG Rev CAACCAAGCTGCAGACATTC; Sox13 For ACTGCTCTCTGGTGAGGCAC Rev GTCTGAGGAGAAGAAGGAGCC; F4/80 For CTTTGGCTATGGGCTTCCAGTC Rev GCAAGGAGGACAGAGTTTATCGTG; Ccl2 For AGATGCAGTTAACGCCCCAC Rev TGTCTGGACCCATTCCTTCTTG; Ccr2 For CCACTGTCTTTGAGGCTTGTTG Rev GCTCTACATTCACTCCTTCCACTG; IFNγ For TGGCTGTTTCTGGCTGTTACTG Rev ACGCTTATGTTGTTGCTGATGG Arg1 For GTGGCAGAGGTCCAGAAGAATG Rev TTGTCAGGGGAGTGTTGATGTC; iNOS For GTTCTCAGCCCAACAATACAAGA Rev GTGGACGGGTCGATGTCAC; F4/80 For CCCCAGTGTCCTTACAGAGTG Rev GTGCCCAGAGTGGATGTCT; CD4 For TCCTTCCCACTCAACTTTGC Rev AAGCGAGACCTGGGGTATCT; Tbet For AGCAAGGACGGCGAATGTT Rev GGGTGGACATATAAGCGGTTC; IL6 For CCAAGAGGTGAGTGCTTCCC Rev CTGTTGTTCAGACTCTCTCCCT; TNF For ATGAGCACAGAAAGCATGATCCGC Rev CCAAAGTAGACCTGCCCGGACTC; Beta Actin For GGCCCAGAGCAAGAGAGGTA Rev GGTTGGCCTTAGGTTTCAGG.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted from lysed tissue samples, and cDNA was transcribed according to previously described protocol [23], [24]. qPCR analysis was then completed utilizing a Light Cycler 480 II (Roche), Sybr Green I Master mix (Roche) and the following primers pairs: Abca1 For GCTGCAGGAATCCAGAGAAT Rev CATGCACAAGGTCCTGAGAA; Mmp2 For GATGGCATTCCAGGAGTCTG Rev CCAGCAAGTAGATGCTGCCT; Rag1 For CTGAAGCTCAGGGTAGACGG Rev CAACCAAGCTGCAGACATTC; Sox13 For ACTGCTCTCTGGTGAGGCAC Rev GTCTGAGGAGAAGAAGGAGCC; F4/80 For CTTTGGCTATGGGCTTCCAGTC Rev GCAAGGAGGACAGAGTTTATCGTG; Ccl2 For AGATGCAGTTAACGCCCCAC Rev TGTCTGGACCCATTCCTTCTTG; Ccr2 For CCACTGTCTTTGAGGCTTGTTG Rev GCTCTACATTCACTCCTTCCACTG; IFNγ For TGGCTGTTTCTGGCTGTTACTG Rev ACGCTTATGTTGTTGCTGATGG Arg1 For GTGGCAGAGGTCCAGAAGAATG Rev TTGTCAGGGGAGTGTTGATGTC; iNOS For GTTCTCAGCCCAACAATACAAGA Rev GTGGACGGGTCGATGTCAC; F4/80 For CCCCAGTGTCCTTACAGAGTG Rev GTGCCCAGAGTGGATGTCT; CD4 For TCCTTCCCACTCAACTTTGC Rev AAGCGAGACCTGGGGTATCT; Tbet For AGCAAGGACGGCGAATGTT Rev GGGTGGACATATAAGCGGTTC; IL6 For CCAAGAGGTGAGTGCTTCCC Rev CTGTTGTTCAGACTCTCTCCCT; TNF For ATGAGCACAGAAAGCATGATCCGC Rev CCAAAGTAGACCTGCCCGGACTC; Beta Actin For GGCCCAGAGCAAGAGAGGTA Rev GGTTGGCCTTAGGTTTCAGG.…”
Section: Methodsmentioning
confidence: 99%
“…IL-6 expressed in hepatocytes, and its level in the blood, correlates positively with the degree of liver inflammation, and fibrosis (46). Another key cytokine in NAFLD is interleukin-17 (IL-17) (41). The activation of the IL-17 axis has shown to have a central role in the progression from NAFLD to NASH in experimental studies (15, 24, 41, 42).…”
Section: An Overview Of the Predictive Role Of General Inflammatory Bmentioning
confidence: 99%
“…Another key cytokine in NAFLD is interleukin-17 (IL-17) (41). The activation of the IL-17 axis has shown to have a central role in the progression from NAFLD to NASH in experimental studies (15, 24, 41, 42). The role of IL-17 family cytokines will be discussed further elsewhere in this paper.…”
Section: An Overview Of the Predictive Role Of General Inflammatory Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of mice hepatocytes, HSCs and Kupffer cells (KCs) with IL-17F had similar to IL-17A, but less pronounced proinflammatory and profibrotic effects upregulating the expression of IL-6, IL-β1, TGF-β and TNF-α mRNA [35]. The research on animal models suggested involvement of both IL-17F and IL-17A in the pathogenesis of NASH, as the activation of IL-17RA by both interleukins was required for NASH progression [36].…”
Section: Discussionmentioning
confidence: 99%